DINAMIKA KEPEMIMPINAN KOLEKTIF PESANTREN SEBAGAI PUSAT PENDIDIKAN ISLAM DI SUMATERA SELATAN - Isnaini, Muhammad (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2010)
The development of schools requires the involvement of a number of the scholars, intellectuals, scientists and society itself. Because the challenges facing schools in the future is very heavy, so its position in the future not only determined Leadership chaplain, but also society at large, called the collective leadership. The elements that can be used as a power movement collective leadership in the management of boarding in the future. First, social relations, namely the negative prejudices of society are based on facts, second, accommodating attitude that is a followup of building social relationships, to eliminate negative prejudices of society, the third, the social relationships built with the chaplain pesantren leaders and public figures and leaders accommodative stance boarding schools to foster understanding and mutual understanding of the chaplain and community leaders, the fourth, a sense of belonging (sense of belonging) and a sense of responsibility (sense of responsibility). fifth, rationality and objectivity that is the application of collective leadership and boarding policy does not depend on individuals, but depending on the institution-system equipped with a mechanism.